A Study on Adoption of Improved Farm Practices by Hill Farmers of Almora District in Uttrakhand - M. L. Roy , Nirmal Chandra , H. L. Kharbikar , Renu Jethi; Pratibha Joshi (Indian Journal of Extension Education, 2014)
Adoption of improved farm practices is being encouraged amongst hill farmers for their socio-economic development. The present study was conducted in Almora, Uttarakhand by taking a random sample of 60 farmers. The objectives were to know the extent of adoption of improved farm practices; relationship of the factors with adoption; and the constraints of adoption. Data were collected during 2011-12 by personal interview through pre-tested structured schedule. Findings showed that majority of the farmers belonged to medium adopter’s category (55.95%). The highest adoption was found in improved varieties of vegetables (71.67%) and least adoption was reported in mushroom production technology (1.67%). Risk bearing ability, change-proneness, level of aspiration, annual income and economic motivation were found to be most significantly correlated factors of adoption. The most serious constraint was identified as weather vagaries (83.33%). The findings of the study can help selecting suitable innovations to diffuse amongst hill farmers of this area.